Catch-per-unit-effort and Biological Data of Nephrops norvegicus from the SW Ireland Spanish Trawl Fishery - Fariña-Pérez, Celso; González-Herraiz, Isabel (2001)
Norway lobster Nephrops norvegicus is a burrowing species inhabiting soft bottoms in the NE Atlantic and Mediterranean. In European western waters (SW Ireland) Nephrops is a comercial species of the bottom mixed fishery prosecuted by fletes from Ireland, France, UK and Spain. A comprehensive collection (1980-2000) of Spanish trawl fishery data and sampling of landings is available. Although Nephrops is a by-catch spcies for the Spanish trawl fleet, some vessels target it mainly during the spring and summer seasoon. This study presents a summarized description of that fishery and catch per unit effort trends. Annual Nephrops length composition by sex, length-weight relationship, sex-ratio and proportion of ovigerous females are given for the referenced period. IEO FPI grant (BOE 06.10.2000, No9). DEMICES project.